2020
DOI: 10.1007/s00018-020-03556-1
|View full text |Cite
|
Sign up to set email alerts
|

Updating dual-specificity tyrosine-phosphorylation-regulated kinase 2 (DYRK2): molecular basis, functions and role in diseases

Abstract: Members of the dual-specificity tyrosine-regulated kinase (DYRKs) subfamily possess a distinctive capacity to phosphorylate tyrosine, serine, and threonine residues. Among the DYRK class II members, DYRK2 is considered a unique protein due to its role in disease. According to the post-transcriptional and post-translational modifications, DYRK2 expression greatly differs among human tissues. Regarding its mechanism of action, this kinase performs direct phosphorylation on its substrates or acts as a priming kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 118 publications
0
48
0
Order By: Relevance
“…DYRK2 is a class II DYRK that has been more intensely studied in terms of its involvement in the events associated with tumor progression. The biochemistry and biology of DYRK2 was covered in recent reviews [ 126 , 127 ], and thus, here, we will center on the activity of this kinase in the context of tumor biology.…”
Section: Dyrk2mentioning
confidence: 99%
See 1 more Smart Citation
“…DYRK2 is a class II DYRK that has been more intensely studied in terms of its involvement in the events associated with tumor progression. The biochemistry and biology of DYRK2 was covered in recent reviews [ 126 , 127 ], and thus, here, we will center on the activity of this kinase in the context of tumor biology.…”
Section: Dyrk2mentioning
confidence: 99%
“…Several clues have been obtained regarding the putative molecular mechanisms responsible for DYRK2-mediated tumor development/progression. Thus, DYRK2 activity appears to affect crucial processes like the cell cycle, DDR, epithelial-to-mesenchymal transition (EMT), the xenobiotic response system and cellular proteostasis [ 127 ]. The activity of DYRK2 has often been linked to its ability to negatively regulate the stability of its target proteins—in particular, through its interaction with the UBR5/EDD-DNA damage-binding protein 1 (DDB1)-DDB1- and cullin 4-associated factor homolog 1 (DCAF1/VPRBP) (EDVP) E3 ubiquitin ligase complex [ 38 ] ( Figure 5 A).…”
Section: Dyrk2mentioning
confidence: 99%
“…3 ). Recent review articles mentioned the conflicting literature on DYRK2 ( 8 , 28 ) and reported that mRNA expression data show that DYRK2 levels are higher in invasive breast carcinoma and lung adenocarcinoma than normal/adjacent tissue control ( 8 , 26 ). However, others maintain that DYRK2 is a major tumor suppressor across all breast cancer subtypes and that DYRK2 depletion promotes proliferation ( 27 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Some of the cancer mutations in Figure 1 B are thought to affect efficient EDVP complex formation ( 3 ). Thus, over the past few decades, many groups have identified various molecular mechanism and substrates for DYRK2 playing diverse roles in cellular growth, proliferation, and developmental processes with a focal point being its role in cancer ( 10 , 25 , 26 , 27 , 28 ).…”
mentioning
confidence: 99%
“…Dual-specificity tyrosine-regulated kinase 2 (DYRK2) is a member of the DYRK family protein kinases containing 4 members in mammals: DYRK1A, DYRK1B, DYRK2, DYRK3, and DYRK4 ( Becker and Joost, 1999 ; Aranda et al, 2011 ; Soppa and Becker, 2015 ; Correa-Saez et al, 2020 ). DYRK2 functions in the DNA damage response by phosphorylating p53 at serine 46, thereby promoting cell apoptosis in response to genotoxic stress ( Taira et al, 2007 ).…”
Section: Regulation Of Siah2 By Protein Kinasesmentioning
confidence: 99%